2016
DOI: 10.1016/j.bbadis.2016.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac ubiquitin ligases: Their role in cardiac metabolism, autophagy, cardioprotection and therapeutic potential

Abstract: Both the ubiquitin-proteasome system (UPS) and the lysosomal autophagy system have emerged as complementary key players responsible for the turnover of cellular proteins. The regulation of protein turnover is critical to cardiomyocytes as post-mitotic cells with very limited regenerative capacity. In this focused review, we describe the emerging interface between the UPS and autophagy, with E3’s regulating autophagy at two critical points through multiple mechanisms. Moreover, we discuss recent insights in how… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 168 publications
(196 reference statements)
0
17
0
Order By: Relevance
“…Protein quality control mechanisms including UPS are essential to normal function of various cells, tissues, and organs through regulating synthesis, folding, trafficking, post-translational modification, assembly, disassembly, localization, and degradation of proteins (Parry & Willis, 2016). The occurrence of the pro-oxidative and proinflammatory states in cardiorenal metabolic syndrome, which include low-grade inflammation, oxidative stress, glycosylation, AGE formation, lipid peroxidation, protein oxidation, endoplasmic reticulum (ER) stress, and cytokine release, perturb the highly redox-sensitive UPS to compromise protein quality control, triggering proteotoxicity and cell injury (Hohn, et al, 2016).…”
Section: Pathophysiology Of the Cardiorenal Metabolic Syndromementioning
confidence: 99%
“…Protein quality control mechanisms including UPS are essential to normal function of various cells, tissues, and organs through regulating synthesis, folding, trafficking, post-translational modification, assembly, disassembly, localization, and degradation of proteins (Parry & Willis, 2016). The occurrence of the pro-oxidative and proinflammatory states in cardiorenal metabolic syndrome, which include low-grade inflammation, oxidative stress, glycosylation, AGE formation, lipid peroxidation, protein oxidation, endoplasmic reticulum (ER) stress, and cytokine release, perturb the highly redox-sensitive UPS to compromise protein quality control, triggering proteotoxicity and cell injury (Hohn, et al, 2016).…”
Section: Pathophysiology Of the Cardiorenal Metabolic Syndromementioning
confidence: 99%
“…A majority of the proteins in cells undergo PTMs by changing their structures and functions by conformational alterations [16]. PTMs of proteins have been shown to affect mitochondrial quality control, thereby exacerbating or alleviating CVDs [17][18][19]. Therefore, the purpose of this review is to summarize the functional changes of intracellular proteins especially mitochondrialrelated proteins by PTMs and their effects on CVDs, particularly myocardial ischemia/reperfusion (I/R) injury, myocardial infarction, and heart failure.…”
Section: Introductionmentioning
confidence: 99%
“…With the UPS also comes the autophagy lysosome system for clearing the aberrant aggregate of proteins and damaged organelles (mitochondria) ( Varshavsky, 2017 ). Accumulating literature evidence emphasizes a key role for cellular autophagy in maintaining homeostasis of cardiac myocytes ( Parry and Willis, 2016 ). Induction of autophagy by rapamycin suppresses pressure overload induced cardiac hypertrophy in mice ( Shioi et al, 2003 ; Mcmullen et al, 2004 ), whereas knockdown of autophagic genes such as Atg5 and Atg7 has shown to induce pressure overloaded cardiomyocyte hypertrophy ( Nakai et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, for instance, an adenoviral overexpression of Atrogin-1 and MuRF1 E3 ligases suppresses the cardiac hypertrophy induced by phenylephrine treatment ( Wertz et al, 2004 ; Maejima et al, 2014 ). These studies will provide novel insight into the E3s and DUBs operated signaling cascades and their distinct role in cardiac myopathies ( Parry and Willis, 2016 ; Brown et al, 2017 ). Different components of UPS have been egressed out as significant drug targets in the treatment of cancer, immunodeficiencies, and neurodegenerative diseases ( Paul, 2008 ; Shen et al, 2013 ; Pal et al, 2014 ; Upadhyay et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%